Study guides

Q: M plus 3 m minus 4 equals 0?

Write your answer...

Submit

Related questions

7 minus 1 times 0 plus 3 divided by 3 equals 8.

x=0

7

-7

X=-3

27 times 3 minus 46 plus 23 equals 58.

It equals 0

(x, y) = (-3, -3) or (3, 3)

18

(-3)-(4)=(-3)+4=1 Minus times minus equals plus. The reason for this we need not discuss.

y equals 3

2x+3-7=0 2x=4 x=2

The answer is 0.

Minus 1 times 0 plus 3 divided by 3 is equal to 1

It is a quadratic equation and its solutions are: x = 3 and x = 5

0+3=3

(0, -3)

so, if 2 minus Ln times 3 minus x equals 0, then 2 minus Ln times 3 equals x, therefore 2 minus Ln equals x divided by three, so Ln + X/3 = 2 therefore, (Ln + [X/3]) = 1

minus 5

3 + 0 = 3

6 plus 4 minus 2 plus 2 minus 3= 7 :)

you do 3 plus 5 first then you get 8 you have to find out what minus 7 equals 8

If a equals 3 and b equals minus 5 then a minus b equals what

The centre is (3,-1) and the radius is sqrt(10).

3 + -3